Narasi Ingatan Emosional Perempuan Tionghoa sebagai Resistensi Patriarki dalam Novel Dari dalam Kubur: Perspektif Psikologi Feminis Karen Horney - Ismawati, Ismawati; Farhah, Eva; Warto, Warto (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
Literary narratives in the context of historical trauma play a role in shaping collective memory and gender resistance, especially for Chinese women during the New Order era. This study aims to analyze interpersonal relationships in emotional memory narratives as resistance by Chinese female characters in Soe Tjen Marching's novel Dari dalam Kubur. Therefore, this study is a descriptive qualitative study with a literary discourse analysis approach based on Karen Horney's feminist psychology theory (1973;1937). The main stages of analysis include the identification of gender trauma discourse, the categorization of three styles of interpersonal relationships (approaching, opposing, and distancing), the analysis of the representation of New Order mental trauma, and a study of the historical context that reflects the dynamics of patriarchal power. This model is relevant for describing literary narratives with psychological resistance strategies against historical trauma memories. The data collection method used was to document the discourse of the novel through in-depth reading and recording elements of resistance. In the data analysis stage, this study used Horney's interpersonal style analysis scheme (1973; 1937) and a trauma study approach in literature. The results of the study show that interpersonal relationships (tendencies to approach, oppose, or distance oneself) through Chinese female characters become a symbolic resistance strategy, not merely a neurotic fulfillment, but a transformation of the subaltern position into an active subject that opposes patriarchal ideology and the history of marginalized women within the collective sphere of the state and family.